Families Are Changing: What About the Policies? Between Good Intentions and Good Practices - Carrà, Elisabetta; Di Rosa, Roberta Teresa (Italian Sociological Review, 2022)
The pandemic crisis has, on the one hand exacerbated the fragility of many Italian families, but on the other hand it has also reconfirmed the remarkable resilience of family relationships, with families having once again shown that they know how to react to the strong and rapid changes caused by the emergency, with an equally strong and rapid response capacity. As is well known, one of the pillars on which the Italian welfare system is based is family welfare, i.e. the set of caregiving and mutual support practices implemented within family relationships that make it possible to compensate for the shortcomings of public welfare in terms of both cash and in-kind support. Actually, the “familist” model, beyond the “amoral” face painted by Banfield, represents an indispensable resource for Italian welfare: families have been forced to find (and most times they have succeeded) compensatory mediations to the often dissimilar and contradictory requests that the institutions have made to the various categories of citizens. [...]